THE AIR DEFENSE IDENTIFICATION ZONE (ADIZ) INDONESIA IN ORDER TO ENSURE SECURITY IN THE AIR REGION JURISDICTION OF NATIONAL JURISDICTION (Universitas Perrtahanan Indonesia (UNHAN), 2022)
For the purpose of tracking down and identifying aircraft detected by radar, the Air Defense Identification Zone (ADIZ) was established as a support facility for the national air defense system.Airspace above the high seas, which borders other countries' sovereignty, usually extends from the territorial area of the founding country. Analysis of ADIZ Indonesia's role in supporting Indonesia Air Force airspace security was a primary goal of the study. Qualitative methods are employed in this study. Data was gathered through a combination of direct observation, in-depth interviews, and documentationAccording to the findings of the study, the identification zone for ADIZ should be outside of national airspace sovereignty in order to identify foreign aircraft entering national airspace sovereignty. ADIZ Indonesia developed will be adhered to by countries if supported by adequate defense equipment. ADIZ Indonesia, which is supported by adequate defense equipment, will be obeyed by other countries. If inforcement is carried out firmly and continuously accompanied by diplomatic efforts by the Minister of Foreign Affairs and software synchronization that regulates the airspace above the Indonesian Archipelagic Sea Lane. The suggestion of this research is that efforts are needed to optimize the implementation of ADIZ Indonesia, which can be implemented and adhered to by other countries if the government of Indonesia can support the needs of the Indonesian Air Force weapon system. For this reason, commitment from government and relevant stakeholders is needed in overcoming the existing problems.Keywords: implementation, identification zone, air defense, national jurisdiction, regional security